2019
DOI: 10.3844/ajabssp.2019.86.94
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Growth and Yield Parameters of Soybean (Glycine max (L.) Merr.) under the Influence of Bradyrhizobium japonicum in Kipushi (The Democratic Republic of Congo)

Abstract: This study aimed to evaluate the correlations between different agronomic parameters and their contribution to soybean performance under Bradyrhizobium japonicum influence. The experiment was carried out at Kanyameshi (Kipushi), following a Split Plot design, with three strains of Bradyrhizobium japonicum (GraphExTM, Bradyrhizobium sp and Sojapak ® 50) and four soybean varieties (TGX 1740-7F: V1, PAN 1867: V2, TGX 1880-3E: V3 and LUKANGA: V4). The strongest correlations were obtained between fresh biomass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Although this experiment was set in a greenhouse using cultivation pots, a significant positive correlation between the occupancy rate of USDA 110 and shoot dry weight of soybean plants was noted (r = 0.86, p = 0.03). A positive correlation between soybean growth and yield has been reported in previous study [59][60][61][62]. In the present study, yield was positively correlated with plant height (r = 0.35) and shoot dry weight (r = 0.75), albeit without significant differences (Figure 3).…”
Section: Correlation Between the Occupancy Rate Of Indigenous Bradyrh...supporting
confidence: 83%
“…Although this experiment was set in a greenhouse using cultivation pots, a significant positive correlation between the occupancy rate of USDA 110 and shoot dry weight of soybean plants was noted (r = 0.86, p = 0.03). A positive correlation between soybean growth and yield has been reported in previous study [59][60][61][62]. In the present study, yield was positively correlated with plant height (r = 0.35) and shoot dry weight (r = 0.75), albeit without significant differences (Figure 3).…”
Section: Correlation Between the Occupancy Rate Of Indigenous Bradyrh...supporting
confidence: 83%
“…This implies that the value increase of one of this parameter leads to an increase in the parameter to which it is significantly correlated (Shivananda et al, 2013;Kasu-Bandi et al, 2019). Indeed, the positive link between this parameter is an important indicator in the conduct of the Rough lemon.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%
“…The results revealed similar effects between different rhizobial strains on pH, Nitrogen, C/N ratio and soil organic matter at flowering and harvest in both study sites (p>0.05). Several studies have shown that the success of inoculation depends not only on the strain itself, but also on its ability to withstand poor environmental conditions (Smil, 2002;Thies et al, 1991;Nazih et al, 1993;Tshibuyi et al, 2019) on the one hand and, on the other hand, to survive in the soil as saprophytic microorganisms beyond the first month following the inoculation (Gibson and Harper, 1985). The pH under the inoculated treatments remains close to neutral compared to the control inoculated in Kanyameshi site at harvest.…”
Section: Discussionmentioning
confidence: 99%